Konsep Kesalahan dan Kelalaian pada Penyelenggaraan Internet Service Provider (ISP) - Anwar, Chairul; Suryahartati, Dwi; Windarto, Windarto (Universitas Jambi, Fakultas Hukum, 2025)
Internet access (ISP) implementation is based on Law No. 36/1999 on telecommunications. Internet poles and fiber optic cables are often located next to PLN electricity poles. Many people have been disturbed by the presence of unlicensed poles and chaotic cables. The law regulates the use of land and buildings belonging to individuals for telecommunications implementation purposes and requires the consent of the relevant parties. However, this is rarely realized, resulting in similar issues in various places. This study aims to determine and analyze the provider's obligations as the implementing party and the indicators of errors and omissions in ISP implementation. The study employs normative legal research methodologies, encompassing the analysis of legislation and additional secondary data. This study found that providers are responsible for goods under their control. The aggrieved community can hold providers accountable for clear problems resulting from their errors or negligence. It is expected that adjusting existing rules to the status quo will address the problem of fiber optic poles and cables for communities in various regions with similar cases. This will make providers more careful when implementing the internet.